Pengembangan Sistem Nota Dinas Elektronik dengan Tanda Tangan Elektronik Studi Kasus PT Andal Rancang Multi Solusi (Arm Solusi) - Kukuh Fajar Ribawanto; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Andal Rancang Multi Solusi (ARM Solusi) is a technology company that is working on improving its service products, namely Coofis NDE (Collaboration Office Nota Dinas Elektronik). Coofis NDE has features to compose and send letters, receive incoming letters, and dispositions. Some things are less efficient when making letters have to save before seeing the results. It can cause repetition in fixing the letter if the results are not correct. The system also does not have feature electronic signatures, so it is incomplete in accelerating the process of validating result letters. From these problems, this research will try to overcome them. This research uses the waterfall model method. The design phase produces sequence diagrams, class diagrams, physical data models, and low-fidelity interface designs. The implementation phase uses the Angular framework for the front-end and Django for the back-end. For the testing phase, do compatibility testing from the browser side, validation testing, and User Acceptance Testing (UAT). Compatibility testing concluded that the system is still not completely secure in some browsers because of a CSS support problem. The results of the validation test get a value of 100% valid from 28 test cases. In the UAT test, the average result is 92% acceptance index from 5 samples of system users, which means that the system development is very well received.